PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA GABUNGAN KELOMPOK TANI "TANI JAYA" KAMPUNG SIDODADI KECAMATAN BANGUNREJO - Puji, Kemala; Prasetyo, Oka; Chandra, Ade (TECHNOBIZ : International Journal of Business, 2024)
Leadership style and work discipline play an important role in improving performance at GAPOKTAN “Tani Jaya”. This study aims to examine the effect of leadership style and work discipline on performance at GAPOKTAN “Tani Jaya” Sidodadi Village, Bangunrejo District, Central Lampung Regency. The population in this study were all farmers who were members of GAPOKTAN “Tani Jaya” in Sidodadi Village. Data analysis using multiple linear regression, descriptive analysis test, hypothesis testing and coefficient of determination. The results of this study indicate that simultaneously the variables of leadership style and work discipline have a significant effect on performance at GAPOKTAN “Tani Jaya”. While partially leadership style and work discipline also have a significant effect on performance at GAPOKTAN “Tani Jaya” Sidodadi Village, Bangurejo District, Central Lampung Regency. The coefficient of determination is 0.561 which explains that the effect of leadership style and work discipline on the performance variable of GAPOKTAN “Tani Jaya” is 56.1%. It is expected from the results of this study that the Chairman of GAPOKTAN “Tani Jaya” continues to develop his leadership style and farmers who are members of GAPOKTAN “Tani Jaya” continue to improve their work discipline to get maximum performance.